Benefits of vacuum-assisted closure therapy over standard treatments for infected and chronic non-healing wounds after kidney transplantation - A. V. Shabunin; I. P. Parfenov; P. A. Drozdov; O. D. Podkosov; O. V. Paklina; I. V. Nesterenko; D. A. Makeev (Вестник трансплантологии и искусственных органов)
Objective: to evaluate the effectiveness of vacuum-assisted closure (VAC) therapy in comparison with standard treatments for infected and chronic non-healing wounds after kidney transplantation. Materials and methods. From June 2018 to November 2019, 75 kidney transplants from deceased donors were performed at the Transplantation Ward of Botkin City Clinical Hospital. There were 47 men (62.6%) and 28 women (37.4%). Standard surgical technique was used. Immunosuppressive therapy was carried out according to a three-component scheme with anti-CD25 monoclonal antibody induction (basiliximab) intraoperatively and on day 4. All patients received antibiotic therapy with protected third-generation cephalosporins for 7 days after surgery. Postoperative complications were evaluated according to the Clavien-Dindo classification. Standard methods, including daily dressings using modern dressing materials (group I) and VAC therapy (group II) were used for treating infected and chronic non-healing wounds. Results. 30-day mortality in the postoperative period was zero. Postoperative complications were recorded in 11 patients (14.6%), of which 7 had postoperative wound complications. Group I included 3 patients (1 with a Klebsiella pneumonia-infected wound and 2 with chronic non-healing wounds and no microflora growth). Group 2 had 4 patients (3 with infected wounds (Esherichia coli - 1, Klebsiella pneumonia - 2) and 1 with chronic non-healing wound). Complete cleansing of wound, absence of bacterial growth according to the microbiological examination, and maturation of granulations according to histological examination were considered as the criteria upon which a wound could be sutured in both groups of patients. The average time between the start of treatment and secondary suturing in group 1 patients was 33.11 ± 5.43 (28-37) and 15.01 ± 3.15 (13-17) days in group 1 and group 2 respectively. Conclusion. VAC therapy in patients with wound complications resulting from kidney transplantation, in comparison with standard treatment, can achieve rapid wound cleansing, acute inflammation relief and accelerated maturation of mature granulation tissue, thereby improving treatment outcomes in this category of patients.